Organizational Learning in Higher Education Institutions. Case Study of a Research Group - Rodriguez-Lora, Vanessa (2021)
Introduction. Knowledge is considered today as one of the most important factors in organizations since that allows them to react to changes in the environment, as the establishment of flows within them allows them to be more competitive and innovative. But what happens when that knowledge is in an educational institution, in which, despite being considered its most important asset, the appropriate knowledge networks are not established so that they can respond to these changes, preventing the development of internal and external transfer processes. This original article is derived from the doctoral thesis titled Organizational Learning as a Mechanism of Knowledge Transfer in Higher Education Institutions. Objective. To show how university research groups behave as learning organizations to identify the factors that allowed developing that learning. Method. For this, a qualitative study of a descriptive-evaluative, non-experimental, single-measure type was designed, in which a triangulation of instruments was used to corroborate and validate the findings through the use of tools such as interviews, surveys, participant observation, and analysis of social networks. Results. The results obtained were analyzed with specialized tools for qualitative data as MaxQDA and Ucinet used in mixed research methods. Conclusions. The study allowed identifying how education institutions and, in particular, research groups could become learnin